Atraumatic restorative treatment in Brazilian schoolchildren: 12 months preliminary clinical results - Patrícia Almada Sacramento; Ana Flávia Sanches Borges; Raphaela Farias Rodrigues; Regina Maria Puppin-Rontani (Brazilian Dental Science)
Objective: To evaluate the clinical efficacy between two GICs, Fuji IX (GC Int. Corp.) and Ketac Molar (3M ESPE), used in Atraumatic Restorative Treatments (ART).